IKATAN KIMIA SEBAGAI PERSPEKTIF HUBUNGAN MANUSIA DENGAN ALLAH SWT DALAM TINJAUAN HADIS NABI SAW - Ismail Pane; Amanda Hervina (MAHABBAH: Jurnal Ilmu Ushuluddin Dan Pemikiran Islam, 2026)
This study examines the concept of chemical bonding as an analogy for understanding the relationship between humans and Allah SWT from the perspective of the hadiths of Prophet Muhammad SAW. Chemical bonding, which serves as the foundation for the formation of compounds in chemistry, is analogized to the spiritual attachment of humans to their Creator. The purpose of this study is to explore the concept of chemical bonding as an analogy for understanding the relationship between humans and Allah SWT based on the perspective of the hadiths of Prophet Muhammad SAW. This research employs a qualitative descriptive method with a library research approach, integrating scientific literature in the field of chemistry with Islamic references, particularly hadith literature. The findings reveal that various types of chemical bonds, such as ionic, covalent, and metallic bonds, as well as the concepts of valence electrons and polarity, can be associated with Islamic values such as submission to Allah, mutual assistance in goodness, Islamic brotherhood (ukhuwah Islamiyah), and the importance of choosing a righteous environment. The study concludes that understanding scientific concepts in chemistry can serve as a medium for spiritual reflection to strengthen faith, thereby making the learning of chemistry more meaningful and contributing to the development of strong character and spirituality.